PENGGUNAAN WARNA PADA KLASIFIKASI BAHAN PUSTAKA DI PERPUSTAKAAN MAN 2 PONTIANAK - Dwi Nur Rizma; Sahidi Sahidi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
Classification in school libraries generally uses the DDC system. However, with the classification system, users are not familiar with collection searches that only use classification numbers. This study aims to determine the process of using color in the classification of library materials and the obstacles faced by library staff in the coloring process at the MAN 2 Pontianak Library. The research method used is descriptive qualitative method. Data collection techniques using observation techniques, interviews with 5 informants, and documentation. The data analysis technique uses data collection, data reduction, data presentation, and drawing conclusions. The results show that the process of using color in the classification of library materials starts from the classification of the collection, coloring with Microsoft Excel, printing labels, and attaching labels to the collection. The obstacles faced were the inaccuracy of the staff when coloring, fading colors on old labels, problematic facilities, and students who have color blindness, although this has not been found in schools.